2000
DOI: 10.1038/sj.leu.2401962
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of the United Kingdom Medical Research Council protocols for childhood acute lymphoblastic leukaemia, 1980–1997

Abstract: Results of three consecutive completed UK trials (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997) for childhood lymphoblastic leukaemia are presented. National accrual has progressively increased so that over 90% of all the country's ALL cases were treated on the latest trial reported, UKALLXI. From 1980 to 1990, event-free and overall survival progressively improved, following adoption of an American therapy template and use of two post-remission int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 19 publications
4
75
0
Order By: Relevance
“…The failure of higher leukocyte count increments to adversely affect outcome has also been noted in T-cell ALL, [25][26][27][28] another leukemia usually presenting with a high leukemic cell burden. Previous studies have shown that in t(11;19) ALL, T-lineage cases have a more favorable outcome than B-lineage cases.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of higher leukocyte count increments to adversely affect outcome has also been noted in T-cell ALL, [25][26][27][28] another leukemia usually presenting with a high leukemic cell burden. Previous studies have shown that in t(11;19) ALL, T-lineage cases have a more favorable outcome than B-lineage cases.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for risk-directed therapy underpinning these huge gains in survival from childhood 1971 -1975 1976 -1980 1981 -1985 1986 -1990 1991 -95 1996 -2000 Average annual change a Childhood, 1986;Eden et al, 2000;Gibson et al, 2005). All the studies that have examined long-term survival in childhood cancer patients, in Britain and in other countries, have concluded that survivors experienced excess mortality beyond 5 years after diagnosis, with a 10.8-fold excess in all-cause mortality in the United States and Nordic countries (Hawkins, 1989;Robertson et al, 1994;Mertens et al, 2001;Möller et al, 2001;Cardous-Ubbink et al, 2004).…”
Section: Time Since Diagnosis Relative Survival (%)mentioning
confidence: 99%
“…The increase in survival is attributed to the use of intensive chemotherapy, combined with other modalities of treatment, and to improved supportive care (Eden et al, 2000;Gibson et al, 2005). The number of childhood leukaemia survivors who are alive more than 10 years after diagnosis has increased as a result, and there are currently over 5500 long-term survivors in Great Britain.…”
mentioning
confidence: 99%
“…Current chemotherapy treatment protocols induce complete remission (CR) in Ͼ95% of children with ALL and disease-free survival (DFS) rates are exceeding 70%. [1][2][3][4][5] The patients are considered to be in morphological remission when blast cells compose less than 5% of the bone marrow (BM) cell population. However, relapses of disease do occur, suggesting that some of the leukemic blasts are resistant to chemotherapy and can persist in very small amounts in the BM.…”
Section: Introductionmentioning
confidence: 99%